Asuhan Keperawatan Medikal Bedah Pada Pasien Ca Mammae Post Mastektomi Di Ruang Rawat Inap Bedah Wanita RSUP Dr. M. Djamil Padang - Zulfadhilla .; Linda Marni; Aulia Asman; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Breast cancer (Carcinoma Mammae) is a condition in which cancer cells have lost their normal control and mechanisms, resulting in abnormal, rapid, and uncontrolled growth occurring in breast tissue. According to the International Agency for Research on Cancer of the World Health Organization (WHO), in 2022 Indonesia ranked 8th out of 10 countries. Breast cancer accounts for approximately 16.2% of all cancer cases (66,271 breast cancer cases). West Sumatra ranks third among provinces with 0.9% of cases (2,285 cases) and an average mortality rate of 17 per 100,000 population. Data from the medical records of Dr. M. Djamil General Hospital in Padang show 474 cases (2025), indicating an annual increase in breast cancer cases. This study aims to provide nursing care for patients with post-mastectomy breast cancer in the women’s surgical inpatient ward at Dr. M. Djamil General Hospital in Padang on February 12, 2026. The assessment of Mrs. A revealed that the client complained of pain at the postoperative wound site on the left side of her chest, with the wound covered by a bandage. Four diagnoses were identified for Mrs. A: acute pain related to a physiological injury, impaired skin integrity, body image disturbance due to changes in body structure and shape, and activity intolerance. Interventions included pain management, skin integrity care, relaxation therapy, and body image promotion over a 5-day period. The evaluation showed that the problems were resolved within 5 days, from February 12–17, 2026, in SOAP format. It is hoped that this final project can serve as a source of information and knowledge for patients and their families regarding breast cancer.